2022
DOI: 10.3389/fpubh.2022.876266
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Between Hospital Service Quality, Patient Trust, and Loyalty From a Service Encounter Perspective in Elderly With Chronic Diseases

Abstract: Based on the service encounter perspective, this study combines theoretical foundations for such factors as service quality and the characteristics of the hospital service industry to develop a research model scale to investigate whether the quality of hospital services affects patients' perceptions of health service encounters, trust, and loyalty. Nowadays, with the advancement of medical technology, patients pay more attention to the quality of medical services and good service encounters provided by healthc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 45 publications
(83 reference statements)
0
16
0
4
Order By: Relevance
“…Many previous studies have shown that product/service quality is an important determinant of satisfaction (36,37). In the healthcare context, this finding is also supported (16,17,38). Accordingly, the quality of a doctor's service has a positive impact on patient satisfaction.…”
Section: Doctor Quality As a Moderatormentioning
confidence: 76%
“…Many previous studies have shown that product/service quality is an important determinant of satisfaction (36,37). In the healthcare context, this finding is also supported (16,17,38). Accordingly, the quality of a doctor's service has a positive impact on patient satisfaction.…”
Section: Doctor Quality As a Moderatormentioning
confidence: 76%
“…This is an open access article under the CC-BY license dapat memenuhi harapan akan membuat pasien terus menggunakan jasa rumah sakit (Shie et al, 2022). Menciptakan suasana aman dan nyaman bagi pasien merupakan tugas pihak rumah sakit untuk memuaskan pasien (Abdurahman et al, 2017).…”
Section: Apabila Peningkatan Kualitasunclassified
“…Kualitas layanan yang berkualitas merupakan penanda waktu penyelesaian berada dalam batas yang dapat diterima pasien atau pasien tidak merasa jenuh dengan lamanya waktu yang mereka habiskan untuk melakukan kunjungan di rumah sakit khususnya instalasi rawat jalan (Shie et al, 2022).…”
Section: Tabel 2 Analisis Waktu Penyelesaian Dan Kepercayaan Pasien D...unclassified
“…Good doctor-patient communication will make patients open their hearts, trust doctors, and prefer cooperation, so that doctors could understand patients' conditions and make effective diagnosis in time ( 12 , 13 ). Higher service quality at the hospital leads to higher customer trust, a better customer experience, and a stronger DPR ( 14 ). Communicating improves patient satisfaction and decreases lawsuits.…”
Section: Introductionmentioning
confidence: 99%